Exploring the impact of Shariah training on Islamic banking employees in Pakistan - Ali, Syed Ahmad; Hassan, Arif; Omar, Azura (International Association of Islamic Banks, Karachi, 2017)
The paper explored the need and role of Shariah training of Islamic banking employees in Pakistan. It also examined the effect of such training on employees' commitment and attitude towards Isalmic banking. The study used qualitative approach in which semi-structured interviews of Islamic banking employees in Pakistan were conducted online using skype. The research appeared to be among the few on this subject and fulfills the need to understand training needs and its role in the context of Islamic banking employees in Pakistan. The findings revealed that employees working in Islamic banks perceive Shariah trainingas as a necessity to work for and to continue their Islamic banking operations. For different levels of Shariah training, a step by step approach was suggested - basic to extensive. Similarly, for Shariah training, it turned out to impact employees motivation, organisational commitment, attitude towards Islamic banking as well as performance.